Nubuatan Amos di Era Digital: Kritik Teologis terhadap Judi Online sebagai Mekanisme Pemiskinan Struktural - Ragil Kristiawan; Pujiati Pujiati (Sekolah Tinggi Teologi Injili Indonesia Ambon, 2026)
The advancement of financial technology in Indonesia has coincided with a significant growth of online gambling platforms that are empirically identified as targeting vulnerable groups through targeted digital marketing mechanisms. This research aims to answer how the Prophet Amos's social critique of economic injustice and exploitation of the poor in the Book of Amos provides a conceptual framework for analyzing the structural impoverishment mechanisms of online gambling platforms. Employing a critical social hermeneutics method that combines exegesis of the Amos text (chs. 2, 5, 8) and analysis of online gambling business models, this study uncovers the continuity between the impoverishment structure criticized by Amos (commodification of vulnerable groups, institutionalized fraud, community disintegration) and the operations of digital gambling platforms. The findings indicate that online gambling constitutes a mutation of an extractive system that reproduces ancient exploitation patterns with technological intensity, necessitating a response that moves beyond legal enforcement towards three concrete directions: transformative regulation that prohibits dark patterns and mandates algorithmic transparency, the development of community-based prophetic digital literacy, and the construction of cooperative digital economic alternatives that embody justice.